Cemeteries of Ilinois : a field guide to markers, monuments, and motifs - Hassen, Harold; Cobb, Dawn (Book collections on Project MUSE., 2017)
"Illinois is home to cemeteries and burial grounds dating back to the Native American era. Whether sprawling over thousands of acres or dotting remote woodlands, these treasure troves of local and state history reflect two centuries of social, economic, and technological change. This easy-to-use guidebook invites amateur genealogists, historians, and cemetery buffs to decipher the symbols and uncover the fascinating past awaiting them in Illinois' resting places. Hal Hassen and Dawn Cobb have combined almost three hundred photographs with expert detail to showcase how cemeteries and burial grounds can teach us about archaeology, folklore, art, geology, and social behavior. Features include: the ways different materials used as gravestones and markers reflect historical trends; how to understanding the changes in the use of iconographic images; the story behind architectural features like fencing, roads, and gates; what enthusiasts can do to preserve local cemeteries for future generations. Captivating and informed, [this book] is the only guide you need to unlock the mysteries of our state 's final resting places."--Amazon.com.